DESIGN AND IMPLEMENTATION OF DATA ENCRYPTION WITH RSA METHOD ON MQTT PROTOCOL FOR SHOOTING SIMULATOR - SISWANTOKO - NIM : 23215342, WISNU
Shooting simulator is a simulation system supporting combat training for personnel in the army of Pussimpur TNI AD. Shooting simulator takes advantage of modern technological advances that can be used as an armed combat training organizer to assess and control an exercise with multiple training methods. The data communication system in the firing simulator uses the MQTT protocol which is a very light and simple publish / subscribe message protocol because the design principle of this protocol is to minimize network bandwidth while trying to ensure the reliability level of its delivery. Although MQTT already supports user authentication in its security system, it does not guarantee that this protocol is safe from interception or data theft. So that more security systems are needed to the data that will be sent through the protocol. Data encryption algorithm used in this research is RSA algorithm because it is a public key algorithm which means using different key for encryption process and its decryption. Test results from the use of RSA algorithm as adder of data security system on MQTT protocol can be done with 100% data encryption accuracy level. While the time required to perform the encryption process on the android device is equal to 122.57 micro seconds per character. On the laptop device encryption process takes 30.64 micro seconds per character, for the process of decryption takes time of 17.66 micro seconds per character. The process of sending data on the MQTT protocol takes 14370.57 micro seconds, while for data transmission encryption of 13328.64 micro seconds.